Method of calculating a washing machine with a propeller activator - Prytula, M. (Запоріжжя : ТДАТУ, 2025)
Small annual production programs of work of technical service points of agricultural enterprises determine the design of a washing machine with small overall dimensions and a volume of a bath for washing solution. Heating of the solution to the working temperature is advisable to carry out with electric heaters, intensification of the cleaning process - with a blade activator.
Keywords: washing machine; propeller activator